Extensive study of flow characters for two vertical rectangular polygons in a two-dimensional cross flow - Gul, Farheen; Nazeer, Ghazala; Sana, Madiha; Shigri, Sehrish Hassan; Islam, Shams Ul (Frontiers in Mechanical Engineering, 2024)
Fluid dynamics problems have a significant impact on the growth of science and technologies all over the world.This study investigates viscous fluid's behavior when interacting with two rectangular polygons positioned vertically and aligned in a staggered configuration. Two physical parameters, Reynolds Number and Gap spacings, are discussed using the Lattice Boltzmann Method for two-dimensional flow. Results are discussed in vortex snapshots, time trace histories of drag and lift coefficient, and power spectra analysis of lift coefficient.Nine distinct flow vortex streets are identified based on increasing gap spacings between the pair of two rectangular polygons. The vortex shedding mechanism is disturbed at small gap spacings and becomes optimal at large gap spacings. Different physical parameters of practical importance, like mean drag coefficient, root mean square values of drag coefficient, root mean square values of lift coefficient, and Strouhal number, approach the single rectangular polygon value at large gap spacings.